Enhancing Prime Editing Efficiency Through Modulation of Methylation on the Newly Synthesized DNA Strand and Prolonged Expression - Xiaosong Han; Xianghua Xu; Youcai Xiong; Guangxing Zhao; Ruigao He; Yinyu Su; Sheng Li; Changzhi Zhao; Xiaoning Xi; Yunxia Zhao; Xuewen Xu; Shengsong Xie; et al. (Advanced Science)
Abstract Prime editors (PEs) have emerged as transformative tools for precision genome engineering, yet their broader application remains constrained by incomplete understanding of repair mechanisms. In this study, it is found that an increase in the methylation level of the CpG sequence on the newly generated strand can increase PE efficiency and that de novo DNA methyltransferases (DNMT3A/3B) are involved in the PE repair pathway. On the basis of these novel findings, the development of an episomal element‐driven PE system (epiPE) achieved through the use of EBNA1/oriP are presented, which increases methylation levels around target sites and prolongs PE expression. A comparative analysis with canonical PE systems, including PE2, lentiPE2, and PE4max, reveals that the epiPE2 system significantly enhances editing efficiency while maintaining minimal insertion and deletion (indels) rates. Specifically, comparing to PE2, the epiPE2 system demonstrated an efficiency enhancement of 2.0 to 38.2‐fold. In addition, the epiPE2 system is capable of efficient multiplex precise gene editing at up to 10 genetic loci in human cells. In conclusion, this findings increase the understanding of the PE repair mechanism, and presents the epiPE2 system as an efficient and multiplex‐capable prime editing tool with potential applications in both basic research and translational studies.